A New Nano Silica Gel Supported by Thionyl Chloride as a Solid Acid for the Efficient Diazotization of Aniline Derivatives: Application and Synthesis of Azo Dyes - Mohammad Mirjalili; Fatemeh Zahed; Alireza Hassanabadi (E-Journal of Chemistry)
A new nano silicagel supported by thionyl chloride as a solid acid was synthesized and used as a increasing the production yield of dye to affect the efficient diazotization of arylamines. The diazonium salts thus obtained were coupled, using standard experimental procedures, to anilines and naphthols to afford the requisite azo dyes in good yield. The diazotization and subsequent azo-coupling generated the related azo dyes at low temperature in short reaction times with a simple experimental procedure.